UMPSA collaborates with Higher Education Institutions in Heilongjiang province and launches the Kaiwu Workshop - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 21 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its international network by establishing strategic collaborations with several leading higher education institutions (HEIs) in Heilongjiang Province, China.